2011
DOI: 10.1016/j.jorganchem.2010.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Study of complexes of platinum group metals containing nitrogen bases derived from pyridine aldehydes: Interesting molecular structures with unpredicted bonding modes of the ligands

Abstract: Keywords Arene ligands Pyridine aldehydes Schiff bases Ruthenium Rhodium and iridium a b s t r a c tA series of mono-cationic dinuclear half sandwich ruthenium, rhodium and iridium metal complexes have been synthesized using ((pyridin-2-yl)methylimino)nicotinamide (L1) and ((picolinamido)phenyl) picolinamide (L2) ligands: , 9; Ir, 10). All the complexes have been isolated as their hexafluorophosphate salts and fully characterized by use of a combination of NMR and IR spectroscopy. The solid state structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…All complexes show that the metal centre adopts the so‐called “piano‐stool” geometry, with the metal coordinated to the pentamethylcyclopentadienyl or p ‐cymene ligand, one chloride ligand and N , N ‐ligand ( 5 and 6 ) or N , O ‐ligand ( 8 and 9 ). In 5 and 6 , the M–N distances follow the trends observed in other common N , N ‐coordinated metal complexes,28 while in 8 and 9 the M–N and N–O distances (Tables 1 and 2) are comparable to those observed in analogous rhodium and iridium (C 5 Me 5 ) complexes 29,30…”
Section: Resultssupporting
confidence: 74%
“…All complexes show that the metal centre adopts the so‐called “piano‐stool” geometry, with the metal coordinated to the pentamethylcyclopentadienyl or p ‐cymene ligand, one chloride ligand and N , N ‐ligand ( 5 and 6 ) or N , O ‐ligand ( 8 and 9 ). In 5 and 6 , the M–N distances follow the trends observed in other common N , N ‐coordinated metal complexes,28 while in 8 and 9 the M–N and N–O distances (Tables 1 and 2) are comparable to those observed in analogous rhodium and iridium (C 5 Me 5 ) complexes 29,30…”
Section: Resultssupporting
confidence: 74%
“…The Ru–Cl bond lengths are 2.4009(6) and 2.4047(4) Å whereas the Ru–N bonds distances lie between 2.071(2) and 2.085(6) Å (Table ) similar to those reported for related arene ruthenium complexes with N , N ' bidentate ligands ,. [15a], The N–Ru–N bond angles range between 76.75(8) and 76.84(5)°, whereas the N–Ru–Cl angles ranged from 83.74(4) to 85.45(4)° as observed in related complexes , …”
Section: Resultsmentioning
confidence: 88%
“…Upon coordination with the metal atom, each metal complex has shown seven signals in the range around 9.00 to 7.30 ppm similar to free ligand, which is, indicated that formation of mononuclear complexes. For all these complexes, the signals of the coordinated dipyridyl and phenyl protons are shifted to considerable downfield as compared to free ligand due to consequence of their coordination to metal atoms 29. Besides these signals, complexes 1 and 5 exhibit a singlet signal at δ = 6.35 ppm for the protons of the benzene ligand.…”
Section: Resultsmentioning
confidence: 97%